Les relations transnationales et l’intégration européenne : Note pour un modèle - Forest, Pierre-Gerlier (Études internationales, 1981)
The hypothesis of European Systems distinct from that or those composed of States is not new. In order to utilize this hypothesis effectively cognizance must be taken, in addition to the multiplicity of actors, of the rivalry of their projects and their strategies. Such an approach to the European reality would contribute to the construction of a new and useful model provided that certain methodological procedures are respected.Research efforts with respect to integration must not be subordinated to the examination of relations of interdependence within the international System. Ostensively structured to renew the problematics of integration, a thesis of that nature is in fact akin to the older « realist » paradigm. Rather, one would hope to benefit from the findings of research respecting transnational relations and to incorporate them with the more institutional concerns of integration theory. This theoretical mix is expressed by a network model, which respects the specific, multiple and hierarchic combination that characterizes integrationist phenomena. The "European network" model possesses two registers. Globally, there is the operator or System of relations that transforms or "translates" relations among groups. At this level, the model makes it possible to effectively describe the makeup of political Europe. Locally, the network is a assemblage of structures or hierarchic and stable sets that assume the form of alliances or of groupings, conflicts or shared ventures. Two further concepts are necessary to activate the network model: those of the "position" and "strategy" of the actors. The former is founded on dynamic oppositions and involves categorization of "major" and "minor" actors whose relations are analyzed by a consideration of the network's structures of order. The concept of "strategy" seeks to give expression to the relationship between the organizational mode of a social group and its representation. By attempting a synthesis of the "Marxist" approach of integration and the study of "transgovernmental" relations, this concept could be applied to the European States.